A Dynamic General Equilibrium Framework of Investment with Financing Constraint - Xie, Danyang; Yuen, Chi-Wa. (Washington, D.C. : International Monetary Fund, 2002)
In this paper, we provide a dynamic general equilibrium framework with an explicit investment-financing constraint. The constraint is intended as a reduced form to capture the balance sheet effects, which have been widely regarded as an important determinant of financial crises. We derive a link between the value of the firm and the social welfare and we find that the value of the firm can be greater with than without the constraint. Our model also sheds light on how the effects of productivity shocks and bubbles may be amplified by the financing constraint.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet